2016
DOI: 10.1130/g37791.1
|View full text |Cite
|
Sign up to set email alerts
|

Insights into cyanobacterial fossilization in Ediacaran siliciclastic environments

Abstract: Ediacaran sedimentary successions are noted for the preservation of microbes and microbial textures on the surfaces of sandstones and siltstones. Although microorganisms have been preserved in coarse-grained siliciclastic sand throughout geologic history, the exceptional preservation of microbes in Ediacaran sediments suggests the potential for a unique taphonomic window. Here, we identify conditions conducive to the fossilization of filamentous cyanobacteria growing in the presence of siliciclastic sand and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…Clay minerals have been suggested to play a key role in preservation of organic matter, with several studies showing a close association between siliciclastic minerals and microbial organisms (McMahon, Anderson, Saupe, & Briggs, ; Newman, Mariotti, Pruss, & Bosak, ; Wacey et al., ). Newman et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clay minerals have been suggested to play a key role in preservation of organic matter, with several studies showing a close association between siliciclastic minerals and microbial organisms (McMahon, Anderson, Saupe, & Briggs, ; Newman, Mariotti, Pruss, & Bosak, ; Wacey et al., ). Newman et al.…”
Section: Discussionmentioning
confidence: 99%
“…Newman et al. () demonstrated through experimental preservation of cyanobacterial mats the potential for clay minerals in suspension to coat bacterial filaments and promote preservation. It has been additionally suggested that the inhibition of growth due to clay mineral coating promotes preservation of soft tissue in bacteria (McMahon et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Two different cyanobacteria filaments were found in the morphotypes M2 and M5, both herbivorous coprolites, and probably produced inside water. According to Newman et al (2016), elevated concentrations of seawater silica and the delivery of suspended clays promote microbial preservation in a few days. Even though the chemical composition of the Urumaco coprolites and microbial material preserved therein are phosphatic, the same composition indicates the microbial remains were rapidly coated by calcium phosphate.…”
Section: Coprolite Fossilizationmentioning
confidence: 99%
“…Interestingly, recent studies on the source of clay particles coatings on cyanobacterial filaments embedded in ancient (Ediacaran) siliciclastic deposits (Newman et al, 2016) suggest a combined, external and authigenic provenance of the fine phyllosilicate encrustations. Control experiments with living filamentous cyanobacteria in siliciclastic sediment and externally supplied by clay suspension confirmed these observations (Newman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%